The effect of technological changes on unemployment in the beverage sector of the South African economy / A.K. Danso - Danso, Alex Kwame (North-West University, 2009)
The ability of the South African economy to absorb labour has been declining since the 1960's, with the manufacturing sector employment declining since 1990. The decline in manufacturing jobs flies in the face of increased output of the sector. This trend is attributed to the application of technology and sophisticated equipments in the manufacturing process leading to a loss of jobs, particularly for unskilled labour. Unemployment in South Africa has become one of the biggest challenges facing the present government. The government in its bid to overcome this major problem is doing everything to get to the crust of the matter, including information on major causes of unemployment in the country. Reduction of unemployment is hugely regarded as a prerequisite for poverty alleviation, a policy that is very close to the heart of the present government. For this singular reason, information on major causes of unemployment in South Africa is becoming increasingly important to policy makers. The objective of this study is to compare the effect of labour and capital on the revenue of the beverage industry in South Africa from 1985 to 2005 using translog production function. The study showed that new technology, due to spending on new capital did not play a significant role in achieving an increase in revenue in the beverage sector. The increase in revenue was rather attributed to an increase in spending on labour. Increasing expenditure on labour by 1% raised revenue by 0, 62% while 1% change in capital expenditure increased revenue by 0,43%. This, in some ways, indicates that the beverage sector of the South African economy is labour-intensive. One could therefore conclude that the beverage industry relies more on labour and does not contribute significantly to unemployment in South Africa. === Thesis (M.B.A.)--North-West University, Potchefstroom Campus, 2008.